Skin involvement in systemic lymphoma of follicular helper T‐cell origin: A cohort study of 57 patients - Romain Stammler; Maxime Battistella; Julien Calvani; Baptiste Louveau; François Lemonnier; Saskia Ingen‐Housz Oro; Nicolas Ortonne; Jean David Bouaziz; Jacqueline Rivet; Marie‐Dominique Vignon‐Pennamen; David Boutboul; Caroline Ram‐Wolff; et al. (Wiley, 2023)
Abstract Background Angioimmunoblastic T‐cell lymphoma (AITL) is one of the most frequent peripheral T‐cell lymphomas (PTCL) in western countries. Skin involvement is common and may reveal the malignancy. Despite its frequency, skin involvement in AITL has been poorly described. Objectives We aimed to analyze the cutaneous expression of PTCL of TFH origin and its prognostic impact. Methods We conducted a multicenter retrospective cohort study by retrieving histopathological reports including the mention 'AITL' or 'PTCL with T‐follicular helper phenotype' (PTCL‐TFH) from five French tertiary hospital centers. Results From 2000 to 2022, we reviewed 382 histopathological records and identified 52 AITL cases and 5 PTCL‐TFH cases with cutaneous involvement. Thirty‐two (56%) patients were males with a mean age of 63 years. Fifty‐six (98%) patients presented with lymphadenopathy, 32 (56%) splenomegaly and 17 (30%) hepatomegaly. B signs were present in 34 (60%) patients. Skin lesions were present on the lower limbs in 44 (77%) patients, trunk in 38 (67%) patients, upper limbs in 35 (61%) and head in 27 (47%). Macules and papules were the most frequent lesions found in 47 (82%) patients, followed by nodules in 10 (17%) patients, erythemato‐squamous plaques in 10 (17%) patients, purpura in 9 (16%), urticaria in 9 (16%) and blisters in 5 (9%) patients. Erythroderma affected seven patients (12%). A skin biopsy was taken in 50 patients and revealed a specific lymphomatous infiltrate in 36 cases. A dominant skin T‐cell clone was detected in 13 out of 17 (76%) patients. Among the 14 patients with a nonspecific dermatitis, various histopathological patterns were observed including interface dermatitis, psoriasiform dermatitis, vasculitis, bullous dermatitis, granulomatous dermatitis and thrombotic vasculopathy. After a median follow‐up of 24 months (range, 0-121 months), median overall survival was 121 months (95% CI, 25.2-NA). At last follow‐up, 33 patients (58%) were alive, 20 (35%) were in complete remission and 7 (12%) were in partial remission; 30 (53%) patients experienced at least one relapse, including nodal relapses in 24 (80%) cases and cutaneous relapses in 12 (40%). Conclusions This study revealed the deep heterogeneity of skin presentations in AITL. Atypical skin presentations were common and included blistering, purpuric and psoriasiform eruptions.